IMPROVEMENT OF FINANCIAL SUPPORT OF RAISING PRODUCT QUALITY WITH THE HELP OF SMART MANAGEMENT INFORMATION SYSTEMS - Sultonali U. Mekhmonov; Mukaddas A. Dzhorobaeva; Maria A. Dzhenalieva; Ulyana V. Ashmarina; Aghavni G. Hakobyan (Proceedings on Engineering Sciences)
We analysed the directions for improving financing for the growth of quality in the conditions of smart production and revealed the advantages and features of their realisation in developing and developed countries. These directions were systematised in the context of factual and prospective use. We also determined their possible modifications given the transformations of economic and technological development. We distinguished the effects of the improvement of financial support in this sphere, which include network, environmental, and social. We demonstrated the necessity of substantiating the possibility of achieving the effects of these categories for the interested parties; this measure is a precondition for their efforts in the creation of favourable financial conditions for the innovative business. The goal of this paper was to identify the directions for improving financial support for raising product quality with the use of smart management information systems. In the course of the research, we used the method of system approach, statistical analysis, the trend method, and comparative analysis. The novel aspect of this paper lies in identifying the factual and prospective directions of improvement of financing smart productions, which ensures an increase in product quality and the creation of new product samples.